PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KELAS X1 SMAN 3 TANAH PUTIH KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Trisnawati, Fenny; ', Nurdayana; ', Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: Given the importance of economic learning level of high school education, the role of teachers is very important to realize the economic achievement of learning goals. A teacher not only provides knowledge about the learning material that will be taught to students, but the teacher should be able to plan an effective learning, so what the learning objectives are achieved. The learning model two stay two stray technique or method two only two guests. Learning is a learning model that begins with the division of the group, and provide opportunities for groups to share results and information. This study aims to improve the learning outcomes of economic subjects graders x1 SMAN 3 white ground rokan districts downstream. Place of research conducted in SMAN 3 white ground. The samples used were students of class x1 totaling 28 people. Data obtained using the testing techniques and observational techniques. Data analysis techniques used are: data analysis activities of teacher, student activity data analysis, analysis of student learning outcomes, the analysis of the average value of learning outcomes. From the results of data analysis that has been done shows that show that their learning outcome Subject Economics X1 grade students of SMAN 3 Tanah Putih Rokan Hilir after a class action implemented by the method Two Stay Two Stray. From the results that have been obtained by the suggested method Two Stay Two Stray is properly implemented, it is expected to be used as an alternative economic learning in schools so as to improve the learning outcomes of economics students and teachers and other researchers to allocate time to exactly fit the RPP and conditions class.Keywords: TSTS Learning Method , Results Learning and Economic